Scapular Free Vascularised Bone Flaps for Mandibular Reconstruction: Are Dental Implants Possible? - Martin Lanzer; Thomas Gander; Klaus Grätz; Claudio Rostetter; Daniel Zweifel; Marius Bredell (Stilus Optimus, 2015)
Objectives: Free fibula flap remains the flap of choice for reconstruction of mandibular defects. If free fibula flap is not possible, the subscapular system of flaps is a valid option. In this study, we evaluated the possibility of dental implant placement in patients receiving a scapular free flap for oromandibular reconstruction. Material and Methods: We retrospectively reviewed 10 patients undergoing mandible reconstruction with a subscapular system free-tissue (lateral border of the scapula) transfer at the University Hospital Zürich between January 1, 2010 and January 1, 2013. Bone density in cortical and cancellous bone was measured in Hounsfield units (HU). Changes of bone density, height and width were analysed using IBM SPSS Statistics 22. Comparisons of bone dimensions as well as bone density were performed using a chi-square test. Results: Ten patients were included. Implantation was conducted in 50%. However, all patients could have received dental implants considering bone stock. Loss of bone height and width were significant (P < 0.001). There was a statistical significant increase in bone density in cortical (P < 0.001) and cancellous (P = 0.004) bone. Conclusions: Dental implants are possible after scapular free flap reconstruction of oromandibular defects. Bone height and width were reduced, while bone density increased with time.